The devil's foot [anglicky] - Doyle, Arthur Conan Sir 1859-1930; Baudet, Stephanie, 1945- (The Sherlock Holmes children's collection, 2021)
You should write about the case of the Devil´s Foot. I am sure your readers would love to hear about the day we almost DIED.